RAPID ASSAY DEVELOPMENT OF DICLOFENAC SODIUM COATED TABLET ASSAY USING FTIR COMPARED TO HPLC METHOD - Nugrahani, Ilma; Dillen, Novensius (International Journal of Applied Pharmaceutics, 2018)
Objective: A lot of coated tablet preparations of diclofenac have been marketed. This research aimed to develop and validate a quantitative analysis method for diclofenac sodium coated tablet using Fourier Transform Infrared (FTIR), which never reported. Methods: The quantification was done by measuring the sample spectra, which then was converted into its derivative. Areas under the curve (AUC) of the derivative spectrums were plotted against the concentrations; corresponding to the calibration graphic. Then, the validation method was carried out by evaluating the accuracy, precision, linearity, range, limit of detection (LOD), and limit of quantification (LOQ). Results: The results showed that diclofenac sodium had a specific peak within the wavenumber range of 1550-1605 cm-1. This area showed linearity to concentration within the range 0.1-1.0% w/w, with coefficient correlation of 0.9998. Recovery was found within 98-102% w/w. The intra and inter-day precision showed a coefficient of variance below 2%. The LOD and LOQ were 0.0127% and 0.0424% respectively. Further, a comparative study was performed, between this method and the compendia method using HPLC. The results showed that the measurement method using FTIR has an advantage in terms of time and cost. Conclusion: Based on all data, it is concluded that FTIR can be used as a valid alternative method. It is faster and more cost-effective for diclofenac sodium coated tablet content determination, compared to the compendia method.